Usability Analysis of the Banyuwangi Smart Kampung Website with the Nielsen Heuristic Model to Improve User Experience and the Efficacy of Digital Services - Aliffatin, Ety Subekti; Margono, Hendro; Caspari, Andrean (Universitas Wijaya Kusuma Surabaya, 2026)
The implementation of digital services through the Smart Kampung website represents a pivotal strategic innovation by the Banyuwangi Regency Government to decentralize and enhance public service delivery. However, the efficacy of these digital interventions is fundamentally contingent upon the website's usability, which directly dictates the quality of user experience (UX) and the overall success of e-government adoption. This research performs an exhaustive usability analysis of the Smart Kampung platform using the ten heuristic principles established by Jakob Nielsen. Employing a descriptive quantitative methodology, the study surveyed 73 active users within the Banyuwangi community using a 20-indicator instrument. The results demonstrate that while the platform excels in aesthetic minimalist design (92% satisfaction) and maintains a strong alignment with real-world conventions (78%), it exhibits significant deficiencies in flexibility and efficiency of use (50% disagreement) and user control and freedom (46% disagreement). These findings suggest a rigid architectural framework that may alienate advanced users and lack intuitive recovery mechanisms. The study recommends the integration of